Impact and Compensation of Rainfall Propagation Effect on Pol-ISAR Imaging of Parabolic Antenna - Xinjie Ju; Xinda Li; Lin Gan; Jiapeng Yin; Chun Shen; Jianbing Li (Remote Sensing)
Orientation is an important parameter to identify the working status of a parabolic antenna. Polarimetric inverse synthetic aperture radar (Pol-ISAR) is an effective approach to sense the parabolic antenna, but the imaging process may be seriously deteriorated by the propagation effect under the rainfall condition. This paper proposes a method to compensate for the propagation effect of rainfall for accurately estimating the orientation parameter of a parabolic antenna from Pol-ISAR images. Numerical simulations show that the impact of the propagation effect for the Pol-ISAR imaging of a parabolic antenna is serious, but it can be well compensated for by the method proposed in this paper.